Platelet shedding of CD40L is regulated by matrix metalloproteinase‐9 in abdominal sepsis. Issue 7 (15th July 2013) - Rahman, M.; Zhang, S.; Chew, M.; Syk, I.; Jeppsson, B.; Thorlacius, H.
Summary: Background and objectives: Platelet‐derived CD40L is known to regulate neutrophil recruitment and lung damage in sepsis. However, the mechanism regulating shedding of CD40L from activated platelets is not known. We hypothesized that matrix metalloproteinase (MMP)‐9 might cleave surface‐expressed CD40L and regulate pulmonary accumulation of neutrophils in sepsis. Methods: Abdominal sepsis was induced by cecal ligation and puncture (CLP) in wild‐type and MMP‐9‐deficient mice. Edema formation, CXC chemokine levels, myeloperoxidase levels, neutrophils in the lung and plasma levels of CD40L and MMP‐9 were quantified. Results: CLP increased plasma levels of MMP‐9 but not MMP‐2. The CLP‐induced decrease in platelet surface CD40L and increase in soluble CD40L levels were significantly attenuated in MMP‐9 gene‐deficient mice. Moreover, pulmonary myeloperoxidase (MPO) activity and neutrophil infiltration in the alveolar space, as well as edema formation and lung injury, were markedly decreased in septic mice lacking MMP‐9. In vitro studies revealed that inhibition of MMP‐9 decreased platelet shedding of CD40L. Moreover, recombinant MMP‐9 was capable of cleaving surface‐expressed CD40L on activated platelets. In human studies, plasma levels of MMP‐9 were significantly increased in patients with septic shock as compared with healthy controls, although MMP‐9 levels did not correlate with organ injury score. Conclusions: Our novel data propose a role of MMP‐9 in regulating platelet‐dependent infiltration of neutrophils and tissue damage in septic lung injury by controlling CD40L shedding from platelets. We conclude that targeting MMP‐9 may be a useful strategy to limit acute lung injury in abdominal sepsis.